Application of the matrixes engineering on the development of minimally processed Hass avocado (Persea americana Mill) with additions of vitamin C and calcium (2012)
Matrixes engineering is a method to obtain functional food that uses the vacuum im-pregnatiuon technique to add components to the structure of porous food. Objective. Determining the effect of adding vitamin C and calcium by means of vacuum impregnation (VI) on the quality parame-ters of minimally processed Hass avocado (Persea americana Mill) Results. The VI process provided better characteristics to the samples treated with it in comparison to those with a fresh treatment, with a reduction of the enzymatic browning (a higher lu-minosity >L* and less red coloring), conservation of the hardness, less microbiological countings and a higher sensorial acceptance Conclusions. Adding vitamins and calcium with the vacuum impregnation technique, VI, is an efficient method to conserve the quality characteristics of the minimally processed Hass avocado samples.Key words: Minimally processed avocado, vacuum impregnation (VI), matrixes engineering, vitamin C, vitamin E, calcium.